VD_FINDINFO Jug / 2014 / 263 vom 19. Mai 2014 - VD Tribunal cantonal (2014)
PRÉSOMPTION D'INNOCENCE, DROIT À UN DÉFENSEUR, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE, PRÉVENU, TÉMOIN | 34 al. 1 LCR, 34 al. 4 LCR, 35 al. 1 LCR, 35 al. 3 LCR, 40 LCR, 44 LCR, 90 ch. 2 LCR, 12 al. 1 OCR, 12 al. 2 OCR, 29 OCR, 8 al. 3 OCR, 10 CPP (CH), 147 CPP (CH), 159 CPP (CH)